Scaffold Diversity Synthesis Delivers Complex, Structurally, and Functionally Distinct Tetracyclic Benzopyrones. Issue 4 (26th April 2018) - Sankar, Muthukumar G.; Roy, Sayantani; Tran, Tuyen Thi Ngoc; Wittstein, Kathrin; Bauer, Jonathan O.; Strohmann, Carsten; Ziegler, Slava; Kumar, Kamal
Abstract: Complexity‐generating chemical transformations that afford novel molecular scaffolds enriched in sp 3 character are highly desired. Here, we present a highly stereoselective scaffold diversity synthesis approach that utilizes cascade double‐annulation reactions of diverse pairs of zwitterionic and non‐zwitterionic partners with 3‐formylchromones to generate highly complex tetracyclic benzopyrones. Each pair of annulation partners adds to the common chroman‐4‐one scaffold to build two new rings, supporting up to four contiguous chiral centers that include an all‐carbon quaternary center. Differently ring‐fused benzopyrones display different biological activities, thus demonstrating their immense potential in medicinal chemistry and chemical biology research. Abstract : Building privileged complexity ! A cascade double annulation strategy employing diverse pairs of zwitterionic and other annulation partners with 3‐formyl chromones provide stereoselective access to complex tetracyclic benzopyrones, displaying ring and functional diversity in a small compound collection.